Constraining modern day silicon cycling in Lake Baikal - Panizzo, Virginia; Swann, George E.A.; Mackay, Anson W.; Vologina, Elena; Alleman, L.; Andre, L.; Pashley, Vanessa; Horstwood, Matthew S.A. (American Geophysical Union, 2017)
Constraining the continental silicon cycle is a key requirement in attempts to understand both nutrient fluxes to the ocean and linkages between silicon and carbon cycling over different timescales. Silicon isotope data of dissolved silica (δ30SiDSi) are presented here from Lake Baikal and its catchment in central Siberia. As well as being the world's oldest and voluminous lake, Lake Baikal lies within the seventh largest drainage basin in the world and exports significant amounts of freshwater into the Arctic Ocean. Data from river waters accounting for c. 92% of annual river inflow to the lake suggest no seasonal alteration or anthropogenic impact on river δ30SiDSi composition. The absence of a change in δ30SiDSi within the Selenga Delta, through which 62% of riverine flow passes, suggest a net balance between biogenic uptake and dissolution in this system. A key feature of this study is the use of δ30SiDSi to examine seasonal and spatial variations in DSi utilisation and export across the lake. Using an open system model against deep water δ30SiDSi values from the lake, we estimate that 20-24% of DSi entering Lake Baikal is exported into the sediment record. Whilst highlighting the impact that lakes may have upon the sequestration of continental DSi, mixed layer δ30SiDSi values from 2003 and 2013 show significant spatial variability in the magnitude of spring bloom nutrient utilisation with lower rates in the north relative to south basin.